Pengaruh Harga Terhadap Keputusan Pembelian Sepeda Motor Honda Vario Pada PT. Tridjaya Motor Manado - Laurens, Sondakh Kelvin; Kalangi, Johnny A. F.; Walangitan, Olivia F. C. (JURNAL ADMINISTRASI BISNIS (JAB), 2019)
The purpose of this study is to know the price influence on the decision of Honda Vario Motor in PT. Tridjaya Motor Manado. By looking at this current competition sales are tight motorcycles. This type of research is quantitative research and method of collecting data using questionnaire method. And sampling method using purposive sampling. Data from the questionnaire method results are used to test the outcome of validity and reliability. Data validity test results are obtained by all valid question items. Data reliability test results are obtained by all reliable question items. Simple regression test results so that the coefficient is a positive value. The coefficient of determination of the determination test shows R Square to understand how large the free variables can influence the bound variables as well as to measure the magnitude X variable contributions to the variation (up downs) of the variable Y. And the result of determining coefficient of determination suggests that purchasing decisions are influenced by price. The purchase decision has a positive and significant effect on the price of Honda Vario which has been good to increase the consumer purchase decision of PT. Tridjaya Motor Manado.